2006
DOI: 10.1152/ajpgi.00416.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of the different isoforms of cyclooxygenase and nitric oxide synthase during gastric ulcer healing in cyclooxygenase-1 and -2 knockout mice

Abstract: . Role of the different isoforms of cyclooxygenase and nitric oxide synthase during gastric ulcer healing in cyclooxygenase-1 and -2 knockout mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 43 publications
4
39
0
1
Order By: Relevance
“…Previous studies have shown that the impairing actions of nonselective NSAIDs on ulcer healing can be shared by selective COX-2 inhibitors, suggesting a predominant role of COX-2 in ulcer repair (Shigeta et al, 1998;Halter et al, 2001). Nevertheless, current evidence on the expression of COX isoforms in gastric ulcers is conflicting, and a role in ulcer healing also has been proposed for COX-1 (Jackson et al, 2000;To et al, 2001;Schmassmann et al, 2006). Overall, our results, taken together with the inconsistency of previous findings, support the view that COX-dependent mechanisms do not seem to play a predominant role in the impairing actions of COX inhibitors on gastric ulcer healing.…”
Section: Nsaid-activated Gene and Gastric Ulcer Healing 147supporting
confidence: 51%
See 2 more Smart Citations
“…Previous studies have shown that the impairing actions of nonselective NSAIDs on ulcer healing can be shared by selective COX-2 inhibitors, suggesting a predominant role of COX-2 in ulcer repair (Shigeta et al, 1998;Halter et al, 2001). Nevertheless, current evidence on the expression of COX isoforms in gastric ulcers is conflicting, and a role in ulcer healing also has been proposed for COX-1 (Jackson et al, 2000;To et al, 2001;Schmassmann et al, 2006). Overall, our results, taken together with the inconsistency of previous findings, support the view that COX-dependent mechanisms do not seem to play a predominant role in the impairing actions of COX inhibitors on gastric ulcer healing.…”
Section: Nsaid-activated Gene and Gastric Ulcer Healing 147supporting
confidence: 51%
“…NSAIDs are also able to impair the healing of pre-existing gastric ulcers (Halter et al, 2001;Ma et al, 2002;Schmassmann et al, 2006;Colucci et al, 2009), and here again both COX-dependent and COX-independent mechanisms seem to come into play. Current evidence suggests that NSAIDs exert their impairing effects on ulcer healing through the inhibition of COX isoforms.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…COX-1 inhibitor (SC-560; Cayman Chemical) was dissolved at 50 mg/ml in DMSO and further dissolved in PBS in order to gavage a dose of 5 mg/kg in 100 μl. It was administered twice per day beginning 60 hours prior to APAP and continued for 48 hours after APAP injection as previously established (44).…”
Section: Methodsmentioning
confidence: 99%
“…Administration to rats of a selective COX-1 or COX-2 inhibitor did not induce GI injury; however, coadministration of selective inhibitors caused extensive damage, implying that inhibition of both COX isoforms is essential to injury formation (Tanaka et al, 2001). Studies with COX-1 or COX-2 KO mice demonstrated that COX-1 activity promotes intestinal intactness, and COX-2 activity is necessary for healing of ulcers (Schmassmann et al, 2006). That DCF-AG can inhibit both COX enzymes represents a novel finding and offers a possible cause for the enteropathy associated with DCF-AG exposure.…”
Section: Mechanisms Of Toxicity Caused By Diclofenac Acyl Glucuronidementioning
confidence: 99%